2012
DOI: 10.1016/j.jcat.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Ambient pressure X-ray photoelectron spectroscopy during electrochemical promotion of ethylene oxidation over a bimetallic Pt–Ag/YSZ catalyst

Abstract: The electrochemical promotion of the C 2 H 4 + O 2 reaction over a bimetallic Pt/Ag catalyst (Pt:Ag ratio ≈ 1.5) interfaced to yttrium stabilized zirconia (YSZ) has been studied at 0.25 mbar and T = 650 K using X-ray photoelectron spectroscopy as in situ method. Applying a positive potential of 2V causes a relative rate increase in the CO 2 production up to 120%; the electrocatalytic promotion effect is non-Faradaic (≈ 2). An electrochemical promotion is found to occur only at high enough p(C 2 H 4) when a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…[11][12][13][14][15] With a differentially pumped XPS, we extended the p-range of ethylene oxidation up to 1 mbar, which is even about two orders of magnitude higher in p(O 2 ) than in the studies of Vayenas et al We found absolutely the same picture as at low p: EPOC was only observed beyond the rate maximum when a carbon layer starts to build up. [16] Compared to the L factors reported by Vayenas et al which go as high as 3 10 5 , the values in our UHV-type study are quite modest, reaching only 2.4. Most likely, the discrepancy is largely due to the about two-orders-of-magnitude higher pressure of the reactants used in the older studies.…”
contrasting
confidence: 84%
See 1 more Smart Citation
“…[11][12][13][14][15] With a differentially pumped XPS, we extended the p-range of ethylene oxidation up to 1 mbar, which is even about two orders of magnitude higher in p(O 2 ) than in the studies of Vayenas et al We found absolutely the same picture as at low p: EPOC was only observed beyond the rate maximum when a carbon layer starts to build up. [16] Compared to the L factors reported by Vayenas et al which go as high as 3 10 5 , the values in our UHV-type study are quite modest, reaching only 2.4. Most likely, the discrepancy is largely due to the about two-orders-of-magnitude higher pressure of the reactants used in the older studies.…”
contrasting
confidence: 84%
“…[9] How about TPD? Right at the beginning of their note, Vayenas and Vernoux present in Figure 1 O 2 TPD spectra from Pt/YSZ obtained after 18 O 2 adsorption from the gas phase, followed by electrochemical pumping of 16 O from YSZ. Again, the authors are convinced that this figure "leaves little room for any reasonable doubts about the validity of the sacrificial promoter, i. e. two oxygen species mechanism".…”
mentioning
confidence: 99%
“…The correlations found between surface chemistry on electrode and electrochemical device performance have started to provide mechanistic insight for us to improve electrochemical devices. The use of AP‐PES by electrochemical research community is growing rapidly and new AP‐PES instruments and new model cells are being developed for electrochemical research at several synchrotron facilities . Most of the current studies are limited to the gas‐solid interfaces.…”
Section: Ambient Pressure Photoelectron Spectroscopymentioning
confidence: 99%
“…In the last decade the progress in this field has been gigantic and we will now briefly provide a non-exhaustive list of proposed approaches. Depending on the type of synchrotron radiation employed, different methodologies have been put forward: The research using soft X-rays initially was focused on cells using solid oxide electrolytes [6,19,20] as well as on room [10,16,17] and higher [11] temperature proton exchange membrane (PEM)-based electrode assemblies in (wet) gaseous atmospheres. To investigate electrochemical reactions in liquid electrolytes by soft X-ray spectroscopies, an alternative approach uses electron-transparent graphene membranes to separate the liquid reaction environment from the vacuum section of the analysis chamber [13,21].…”
Section: Introductionmentioning
confidence: 99%